An Atypical Case of Rickettsial Spotted Fever Myocarditis Mimicking Weil’s Disease - N. D. B. Ehelepola; G. D. N. R. Kumara; S. A. C. S. Sapurugala; W. M. N. P. Buddhadasa; Wasantha P. Dissanayake (Case Reports in Infectious Diseases)
A 65-year-old previously healthy male presented to us on the fourth day of a febrile illness with headache, arthralgia, myalgia, nausea, cough, chest pain, sore throat, and passing of watery stools and dark urine with a history of exposure to leptospirosis during a dengue outbreak. On examination, there was dehydration and hypovolemia, and an ultrasound scan revealed capillary leakage. His liver transaminases, serum creatine, blood urea, C-reactive protein, and neutrophil percentage were high, and thrombocytopenia was present. Moreover, myocarditis has been detected too. Supportive therapy with intravenous ceftriaxone was administered, considering possible Weil’s disease or dengue hemorrhagic fever with secondary bacterial infection. Serological tests, performed later, diagnosed him with a Rickettsia conorii infection and excluded dengue, leptospirosis, and hantavirus infections. Repeat 2D echocardiograms showed mild improvement of his cardiac failure after one month and a more improvement after eight months. Clinical features of the rickettsial spotted fever group (SFG) and leptospirosis overlap. Leptospirosis is common; thus, the risk of overlooking SFG and diagnosing leptospirosis is likely. Tests for differentiation are unavailable in Sri Lankan hospitals and in many other developing countries. Empirical doxycycline in suspected cases of SFG infections in areas where rickettsioses are prevalent can save lives as in this case.